GE_GERICHTE C/9953/2013 vom 16. Oktober 2015 - GE Cour de justice (2015)
CHANGEMENT DE DÉBITEUR; INTERPRÉTATION(SENS GÉNÉRAL); REPRISE DE DETTE EXTERNE; VICE DU CONSENTEMENT; CRAINTE FONDÉE | CO.1; CO.18; CO.29; CO.30; CO.176